2016
DOI: 10.1016/j.ajo.2016.06.023
|View full text |Cite
|
Sign up to set email alerts
|

Repeatability of Choroidal Thickness Measurements on Enhanced Depth Imaging Optical Coherence Tomography Using Different Posterior Boundaries

Abstract: PURPOSE To assess the reliability of manual choroidal thickness measurements by comparing different posterior boundary definitions of the choroidal-scleral junction on enhanced depth imaging optical coherence tomography (EDI-OCT). DESIGN Reliability analysis METHODS Two graders marked the choroidal-scleral junction with segmentation software using different posterior boundaries: 1) the outer border of the choroidal vessel lumen, 2) the outer border of the choroid stroma, and 3) the inner border of the scle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 43 publications
1
38
0
Order By: Relevance
“…Several authors have reported that EDI-OCT images are not as clear in patients with a thickened choroid [12, 21]. Specifically, it is more difficult to discern the distal boundary of the choroid at the choroid-sclera junction when the choroid is thickened [12].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several authors have reported that EDI-OCT images are not as clear in patients with a thickened choroid [12, 21]. Specifically, it is more difficult to discern the distal boundary of the choroid at the choroid-sclera junction when the choroid is thickened [12].…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, it is more difficult to discern the distal boundary of the choroid at the choroid-sclera junction when the choroid is thickened [12]. In this study, CT was measured in the subfoveal space from the outer surface of the RPE to the proximal edge of the hyperreflective band at the choroid-sclera junction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies suggest that the repeatability of CT measurements may be optimized at the stromal border. 16 These factors all serve to make CT estimation imprecise, necessitating reproducibility studies to guide analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Most studies to date have assessed CT measurement repeatability in healthy eyes, 1623 with a few studies examining CT in diabetic retinopathy and AMD. 15,2427 We hypothesize that the reliability of CT measurements may be less determined by the pathophysiology of particular conditions, than by the type or quantity of overlying retinal fluid in the macula.…”
Section: Introductionmentioning
confidence: 99%